Analisis Efektivitas Pemasaran melalui Influencer terhadap Minat Kunjungan Wisata Alam di Gunung Tunak Lombok Tengah Nusa Tenggara Barat (International Forum of Researchers and Lecturers, 2025)
In line with the development of social media use, the role of influencers in tourism marketing strategies has developed further. This research is aimed at analyzing marketing through influencers in increasing interest in visiting Mount Tunak tourism in Central Lombok. The purpose of this research is to the influence of trust given to influencers. Data was collected through an online survey to 50 respondents who visited the content promoted by influencers. Competition in the world of tourism today is very tight, therefore it is very important to use influencer-based digital marketing. Influencers already have and can personally and effectively reach audiences, so their relevance and credibility are important to research. The results of the research show that using influencer marketing has a significant impact on visitor interest, which is more dominant when there is trust in the influencer. This research is expected to provide guidance for tourism industry players to maximize strategies in digital marketing.